The Internal Medicine Subinternship: A Curriculum Needs Assessment - Sidlow, Robert (Blackwell Science Inc, 2002)
Despite broad acceptance of the internal medicine subinternship rotation by the undergraduate medical education community, only a small fraction of programs provide students with explicit learning objectives. To design a curriculum for the medical subinternship, we surveyed 3 different groups of educational stakeholders—subinternship directors, residency program directors, and housestaff—in order to identify and prioritize the competencies that should be learned during this rotation. This study provides a starting point for the development of a structured curriculum for the fourth-year subinternship rotation.